HUBUNGAN EKSEKUTIF DAN LEGISLATIF DALAM MEWUJUDKAN TRANSPARANSI PERENCANAAN ANGGARAN DI KOTA SURAKARTA TAHUN 2017-2018 - Astuti, Monica; Harsasto, Priyatno (Journal of Politic and Government Studies, 2020)
One key to effective and efficient governance is good budget management. The agencyrelationship between the executive and the legislature in the preparation and determination ofthe Regional Revenue and Expenditure Budget will provide a pattern for the smooth mechanismof government administration in the region. The purpose of this study is to describe the patternof institutional relations and what are the basis for executive and legislative considerations inthe process of preparing and determining the 2017-2018 Surakarta City Budget. The researchmethod used is a qualitative research method. Research instruments with interviews anddocumentary studies conducted on certain sources.Based on the results found in the field research, it is explained that the planning processin Surakarta City is not only a mere formality. The government as the executive and theSurakarta City DPRD Budget Board as the legislature are not only interested in the budgetdiscussion stage, which is often considered to be a "wetland". Budgeting phase is more aboutthe cost calculation. Between the legislature and the executive have a hrmonistic relationshipso that they collaborate to create a budget that is right on target and transparent. This can beseen by obtaining a Fair Opinion without Exception (WTP) opinion by the City of Surakarta.So that the accuracy of the target, timeliness of budgeting, and transparency of the budget hasa positive impact in every budget planned by the executive approved by the legislature.Therefore, the problems that arise in executive institutions that usually carry outopportunistic behavior over the superiority of their information and legislative bodies thatoften use their power do not make them take advantage of this position against the SurakartaCity Regional Budget. This is because the executive and legislative relationship is not markedby the superiority or dominance of one of the forces.Keywords: Agency, Rational Choice, Regional Budget